THE INFLUENCE OF THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY ON THE PROFITABILITY OF MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE 2016-2020: ASPECTS OF ECONOMIC AND ENVIRONMENTAL INDICATORS - Ar Rayyan Bahar; Sakti Brata Ismaya (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to examine the influence of Corporate Social Responsibility on Profitability. The population in this study used a sample of 40 manufacturing companies on the Indonesia Stock Exchange (IDX) from 2016-2020. The method used in this research is purposive sampling which is taken with certain criteria. Profitability is measured by the Return on Asset (ROA) formula. The data analysis method used is Descriptive Statistics, Multiple Regression Analysis, and Classical Assumption Test, while the Hypothesis Test used is Partial Test, Simultaneous Test, as well as Test of Determination. The results of this study indicate that Corporate Social Responsibility Economic Indicators have a positive influence on Profitability as evidenced by a significant value of 0,013, while Corporate Social Responsibility Environmental Indicators do not have a positive effect on Profitability as evidenced by a significant value of 0,949. Meanwhile, Corporate Social Responsibility economic and environmental indicators simultaneously has a positive influence on profitability as proven by a significant value of 0.036, and R square (R^2) which obtained 11% Profitability which can be influenced by Economic and Environmental Corporate Social Responsibility and 89% is influenced by other factors outside the study.